Rosseland and Flux Mean Opacities for Compton Scattering - Poutanen, Juri (The Astrophysical journal, 2017)
Rosseland mean opacity plays an important role in theories of stellar evolution and X-ray burst models. In the high-temperature regime, when most of the gas is completely ionized, the opacity is dominated by Compton scattering. Our aim here is to critically evaluate previous works on this subject and to compute the exact Rosseland mean opacity for Compton scattering over a broad range of temperature and electron degeneracy parameter. We use relativistic kinetic equations for Compton scattering and compute the photon mean free path as a function of photon energy by solving the corresponding integral equation in the diffusion limit. As a byproduct we also demonstrate the way to compute photon redistribution functions in the case of degenerate electrons. We then compute the Rosseland mean opacity as a function of temperature and electron degeneracy and present useful approximate expressions. We compare our results to previous calculations and find a significant difference in the low-temperature regime and strong degeneracy. We then proceed to compute the flux mean opacity in both free-streaming and diffusion approximations, and show that the latter is nearly identical to the Rosseland mean opacity. We also provide a simple way to account for the true absorption in evaluating the Rosseland and flux mean opacities.